Pelatihan Pembuatan Origami Untuk Meningkatkan Kreativitas Anak Bekebutuhan Khusus Di Panti Asuhan Bhakti Luhur Banjarmasin - Getrudis Tutpai; Ermeisi Er Unja; Lucia Andi Chrismilasari; Aulia Rachman (Pusat Riset dan Inovasi Nasional, 2023)
Children with needs require special treatment to help develop their fine motor skills. Through this community service activity it is hoped that it can develop fine motor skills in children with special needs. This activity is carried out using paper media packaged in the art of paper folding or origami. This paper folding art training activity is given to children with special needs with the method of lectures, questions and answers and demonstrations in the form of paper folding training in various forms. The results of this community service show that there has been an increase in knowledge in groups of children with needs where after the activities the children know about the art of paper folding and can practice how to fold paper in various shapes of animals, flowers and stars. It is hoped that accompanying teachers at the Bhakti Luhur Orphanage can do paper folding or other types of art more often to be able to further develop the abilities of children with special needs. Because fun activities like this are more in demand by children.